More Word 6 for Windows - Bradley, Helen (Helen L. C.) (Brisbane : John Wiley and Sons, 1996)
Editing and formatting. Correcting errors. Page formatting. Managing your documents. Mail merging. Styles. High-level formatting. Incorpating other applications. Templates. Working with macros.
Keywords: Word processing; Microsoft Word for Windows; Microsoft Word for Windows; Word processing